Hunting for Improvement: A CIPP-Based Evaluation of the English Tourist Interaction Program at Vocational High School - Aditya Sahrul Akbar; Dinar Martia Azizah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Evaluation of the program is needed as study material for future decision-making. Thus, this research aims to evaluate the context, input, process, and product of the hunting tourist program implemented at SMK Berbudi Yogyakarta Class X with culinary, visual design, and beauty study programs. A qualitative research method was implemented in this research, using the CIPP model developed by Stufflebeam. Observations, interviews, questionnaires, and analysis of documents, both written and in video form, are used as data in fulfilling the CIPP aspects. The research results found that the program context followed clear planning and was under the school's vision. Input evaluation has played a good role, although some aspects need improvement and correction. The evaluation process has been carried out with an initial agreement with good procedures, although there are still aspects that need to be considered, such as time management by participants. Additionally, the product evaluation results have achieved the goals and positive impacts that were set at the beginning. Furthermore, further research can deepen the data on the development of teaching modules for tourist hunting preparation.